Battery diaphragm, preparation method thereof and lithium-sulfur battery containing diaphragm
By using heteroatom doped molecular sieve on the lithium-sulfur battery separator, the dual effects of physical domain limitation and chemical adsorption are achieved, and the problems of polysulfide shuttle effect and cycle stability in lithium-sulfur batteries are solved, and the cycling performance and capacity of the battery are significantly improved.
Patent Information
- Application Number
- CN202311139087.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-05
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-09-05
AI Technical Summary
In practical applications, lithium-sulfur batteries have problems such as electron transfer hindered, low sulfur utilization, damage to the electrode structure, reduced cycle stability and reduced utilization of active materials caused by polysulfide shuttle effect.
By selecting heteroatom-doped molecular sieves with different compositions and structures, it is used to modify the lithium-sulfur battery separator, realize the dual effects of physical domain limitation and chemical adsorption, inhibit polysulfide shuttle, reduce side reactions, and improve the ion transport performance of the separator.
It effectively inhibits the shuttle of polysulfides in lithium-sulfur batteries, reduces side reactions inside the battery, improves the ion transmission performance of the separator, and thus improves the cycling performance and capacity of the battery.
Smart Images

Figure CN119581794A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery diaphragms, and in particular to a diaphragm for a lithium-sulfur battery, a preparation method thereof, and a lithium-sulfur battery containing the diaphragm. Background Art
[0002] As energy demand increases, it is crucial to explore alternative energy storage systems with higher specific capacity to alleviate the over-reliance on lithium-ion batteries. Lithium-sulfur batteries have attracted widespread attention in the next generation of high-energy-density battery systems due to their high theoretical specific capacity (1675 mAh / g) and energy density (2600 Wh / kg). In addition, sulfur resources are low-cost, abundant in reserves, and environmentally friendly, so they are considered to be a promising lithium-ion battery. However, there are still some challenges before the practical application of lithium-sulfur batteries. For example, the inherent insulation of elemental sulfur (S8) and its final discharge product (Li2S) hinders the transfer of electrons in the electrode and also limits the utilization of sulfur. In addition, during the charge and discharge process, the volume expansion of the sulfur cathode is as high as 80%, which inevitably leads to the destruction of the electrode structure and gradually reduces the cycle stability. Most seriously, the "shuttle effect" caused by the dissolution and migration of long-chain polysulfides (LiPSs) in the electrolyte is often accompanied by the deposition and passivation of Li2S on the lithium anode, which greatly reduces the utilization of active materials, thereby seriously reducing the cycle stability and capacity of lithium-sulfur batteries.
[0003] To date, some promising strategies have been explored and adopted to improve the electrochemical performance of lithium-sulfur batteries, including designing sulfur hosts, modifying separators, and optimizing electrolytes. Among them, coating a modified layer on the surface of the separator is considered to be the most effective and economical strategy to block LiPSs shuttling and accelerate the redox kinetics of LiPSs. Commonly used separator modification materials include porous carbon, inorganic compounds, metal-organic framework materials, etc., but they have limited effects, complex synthesis processes, and high costs.
[0004] At present, there are also existing technologies that use molecular sieves to modify the diaphragm, such as CN107546356A and CN103490027A, which use the physical barrier effect of molecular sieves such as ZSM-35, SAPO-34, 3A, and 13X to limit the Li2S x Migration and diffusion in the electrolyte improve battery performance. However, the performance improvement that can be achieved by a single physical action (i.e., screening) is relatively limited.
[0005] In order for lithium-sulfur batteries to meet the needs of the rapid development of new energy electric vehicles and large-capacity energy storage systems, there is still a need to provide battery separators that can achieve further improved performance. Summary of the invention
[0006] The inventors of the present invention have found through extensive research that by selecting molecular sieves with different compositions and structures and using them to modify the lithium-sulfur battery separator, the performance of the battery can be further improved, thereby meeting the above-mentioned needs of the prior art. Specifically, certain heteroatom-doped molecular sieves, preferably certain heteroatom-doped molecular sieves containing lithium, can effectively inhibit the shuttling of polysulfides in lithium-sulfur batteries through physical confinement and chemical adsorption, reduce the side reactions inside the battery, and improve the ion transport performance of the separator, thereby improving the cycle performance and capacity of the battery. Thus, the inventors have completed the present invention.
[0007] The present invention provides a battery separator and a preparation method thereof, and a lithium-sulfur battery containing the separator. The battery separator of the present invention can effectively inhibit the shuttling of polysulfides in lithium-sulfur batteries through physical confinement and chemical adsorption, reduce the side reactions inside the battery, and improve the ion transport performance of the separator, thereby improving the cycle performance and capacity of the battery.
[0008] A first aspect of the present invention provides a battery separator, comprising a polymer matrix film and a composite layer distributed on one side surface of the polymer matrix film, wherein the composite layer comprises a heteroatom-doped molecular sieve and a conductive carbon material, wherein the heteroatom is located in the crystal framework of the molecular sieve.
[0009] Furthermore, in the heteroatom-doped molecular sieve, the heteroatom is at least one of Fe and Sn heteroatoms, preferably Fe or Sn; the topological structure of the molecular sieve is selected from at least one of MFI, MWW, FAU and MOR, preferably MFI.
[0010] Furthermore, in the heteroatom-doped molecular sieve, the heteroatom content is 0.5%-10.0%, preferably 1.0%-7.0%, based on the weight of the heteroatom-doped molecular sieve. The heteroatom content is, for example but not limited to: 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, etc.
[0011] Furthermore, characteristic absorption peaks of Fe appear at 247±5nm, 278±5nm and 621±5nm in the ultraviolet-visible (UV-vis) diffuse reflectance spectrum of the heteroatom-doped molecular sieve; and characteristic absorption peak of Sn appears at 206±2nm in the ultraviolet-visible (UV-vis) diffuse reflectance spectrum of the heteroatom-doped molecular sieve.
[0012] Furthermore, the material of the polymer matrix film is at least one of polyethylene, polypropylene, polyimide, polyacrylonitrile, polyethylene terephthalate, polytetrafluoroethylene, and polyvinylidene fluoride, preferably polyethylene, polypropylene, or a polyethylene / polypropylene composite material.
[0013] Furthermore, the conductive carbon material is at least one of graphene, carbon nanotubes, carbon nanofibers, acetylene black, Super P, and Ketjen black, preferably graphene.
[0014] Furthermore, the thickness of the composite layer is 1-40 μm, preferably 3-20 μm.
[0015] Furthermore, in the composite layer, the mass ratio of the conductive carbon material to the heteroatom-doped molecular sieve is 1:(1-20), preferably 1:(3-9).
[0016] Furthermore, the heteroatom-doped molecular sieve contains lithium, and the content of lithium as an element is 0.1%-5.0%, preferably 0.2%-1.8%, based on the weight of the heteroatom-doped molecular sieve.
[0017] The second aspect of the present invention provides a method for preparing the above-mentioned battery separator, comprising:
[0018] (1) mixing a heteroatom-doped molecular sieve with a conductive carbon material to obtain a mixture;
[0019] (2) dispersing the mixture and the binder in a solvent to obtain a coating slurry;
[0020] (3) coating the coating slurry on one surface of the polymer substrate film and drying it to obtain the battery separator.
[0021] Furthermore, in step (1), the mass ratio of the heteroatom-doped molecular sieve to the conductive carbon material is (1-20):1, preferably (3-9):1.
[0022] Furthermore, in step (1), the method for preparing the heteroatom-doped molecular sieve comprises:
[0023] (S1) H-type molecular sieve reacts with an acid solution to obtain precursor I;
[0024] (S2) The obtained precursor I is mixed with a heteroatom salt and calcined to obtain a heteroatom-doped molecular sieve.
[0025] Furthermore, in step (S1), the topological structure of the H-type molecular sieve is selected from at least one of MFI, MWW, FAU and MOR, preferably MFI. The silicon-aluminum atomic ratio of the H-type molecular sieve is 5-100.
[0026] Further, in step (S1), the acid is selected from at least one of oxalic acid, sulfuric acid, and phosphoric acid, preferably oxalic acid. The concentration of the acid solution is 0.5-5.0 mol / L. The concentration of the acid solution is, for example but not limited to, 1.0 mol / L, 1.5 mol / L, 2.0 mol / L, 2.5 mol / L, 3.0 mol / L, 3.5 mol / L, 4.0 mol / L, 4.5 mol / L, and the like.
[0027] Furthermore, in step (S1), the liquid-to-solid weight ratio of the acid solution to the H-type molecular sieve is 20-70.
[0028] Furthermore, in step (S1), the reaction conditions are: reaction temperature 50-70°C, reaction time 0.5-3h.
[0029] Furthermore, in step (S1), after the reaction is completed, conventional operations such as centrifugation, washing, and drying are performed to obtain the precursor I. For example, the drying conditions are as follows: drying at 50-180° C. for 8-12 hours.
[0030] Furthermore, in step (S2), the heteroatom salt used is selected from one of iron salt and tin salt. For example, the iron salt is selected from at least one of ferrocene, ferrous lactate, and ferric citrate; the tin salt is selected from at least one of dimethyl stannous chloride and dibutyl tin.
[0031] Further, in step (S2), the amount of heteroatom salt (in terms of metal) added is 0.5%-10.0% of the mass of the H-type molecular sieve, preferably 1.0%-7.0%, for example but not limited to 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0% and the like.
[0032] Furthermore, in step (S2), the mixing is physical mixing, and the mixing method includes grinding, ball milling, etc.
[0033] Furthermore, in step (S2), the calcination temperature is 300-600°C, and the calcination time is 2-8h.
[0034] Furthermore, in step (2), the solvent is at least one of deionized water, anhydrous ethanol, N,N-dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide, and N-methylpyrrolidone, preferably N-methylpyrrolidone.
[0035] Furthermore, in step (2), the binder is at least one of polyvinyl alcohol, carboxymethyl cellulose, polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl pyrrolidone, styrene-butadiene rubber and polyacrylate, preferably polyvinylidene fluoride.
[0036] Furthermore, in step (2), the mass ratio of the mixture to the binder is (1-15):1, preferably (6-10):1.
[0037] Furthermore, in step (3), the coating is performed by a method selected from the group consisting of a casting method, a blade coating method, a spray coating method, a spin coating method, and the like, preferably a blade coating method.
[0038] Furthermore, the heteroatom-doped molecular sieve contains lithium, and its preparation method includes: exchanging the heteroatom-doped molecular sieve with a lithium ion solution to obtain a lithium-containing heteroatom molecular sieve.
[0039] Furthermore, the lithium ion solution is at least one of lithium chloride solution, lithium acetate solution and lithium nitrate solution, and the concentration of the lithium ion solution is 0.1-1.0 mol / L. The exchange conditions are: temperature of 40-100°C, time of 1-6h, liquid-solid weight ratio of 10-50, and exchange times of 1-3 times.
[0040] Furthermore, after the exchange is completed, the lithium-containing heteroatom molecular sieve is obtained after conventional operations such as centrifugal washing and drying. For example, the drying conditions are as follows: drying at 80-150° C. for 10-30 hours.
[0041] A third aspect of the present invention provides a lithium-sulfur battery, comprising a positive electrode, a negative electrode and the above-mentioned separator located between the positive electrode and the negative electrode.
[0042] Furthermore, the lithium-sulfur battery further comprises an electrolyte. The positive electrode, negative electrode and electrolyte can be selected from various positive electrodes, negative electrodes and electrolytes used in lithium-sulfur batteries known to those skilled in the art.
[0043] Compared with the prior art, the present invention has the following beneficial effects:
[0044] 1. The present invention selects heteroatom-doped molecular sieves, preferably heteroatom-doped molecular sieves containing lithium, which can effectively inhibit the shuttling of polysulfide in lithium-sulfur batteries through physical confinement and chemical adsorption, reduce the internal side reactions of the battery, and improve the ion transport performance of the diaphragm, thereby improving the cycle performance and capacity of the battery.
[0045] 2. The molecular sieve modified diaphragm of the present invention adopts heteroatom-doped molecular sieve, which can more effectively inhibit the polysulfide shuttle effect in lithium-sulfur batteries through the dual effects of physical confinement and chemical adsorption. On the one hand, the molecular sieve has sub-nanometer regular pores, which can block the migration and diffusion of polysulfides inside the battery through the screening effect (physical confinement). On the other hand, the crystal framework of the molecular sieve contains Fe or Sn heteroatoms, which can act as anchor points, further enhance the connection with polysulfides, and limit the shuttling of polysulfides by chemical adsorption. Through the dual physical and chemical effects brought about by the above composition and structure, the molecular sieve can more effectively suppress the shuttling of polysulfides in lithium-sulfur batteries and reduce the loss of active substances. In the case where the heteroatom-doped molecular sieve further contains lithium, the introduced lithium can provide a large number of sites for the adsorption and transmission of lithium ions in the battery cycle, thereby improving the lithium ion transmission performance of the diaphragm. Therefore, compared with the existing molecular sieve modified diaphragm, the molecular sieve used in the present invention to modify the diaphragm can greatly improve the cycle performance and capacity of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 The UV-visible diffuse reflectance spectrum of the molecular sieve prepared in Example 1;
[0047] Figure 2 The UV-visible diffuse reflectance spectrum of the molecular sieve prepared in Example 2;
[0048] Figure 3 This is the ultraviolet-visible (UV-vis) diffuse reflectance spectrum of the molecular sieve prepared in Comparative Example 2. DETAILED DESCRIPTION
[0049] In order to better understand the present invention, the technical scheme of the present invention is further described below in conjunction with embodiments. The following embodiments are only for illustration of the present invention rather than for limitation.
[0050] In the present invention, the assembly of the lithium-sulfur battery and the testing process of the battery performance are as follows:
[0051] 1. Assembly of lithium-sulfur battery samples:
[0052] First, prepare the positive electrode: mix the active material sublimated sulfur, the conductive agent Ketjen black, and the binder polyvinylidene fluoride in a mass ratio of 6:3:1, add N-methylpyrrolidone to form a positive electrode slurry; coat the positive electrode slurry on aluminum foil and dry it to obtain the positive electrode. Then assemble the 2025 button battery in an argon glove box with a water and oxygen content of less than 0.1ppm: assemble in the order of positive electrode shell, positive electrode, diaphragm, lithium negative electrode, foam nickel, and negative electrode shell, and add 100μL electrolyte. The electrolyte used is a mixed solution of 1,3-dioxolane / ethylene glycol dimethyl ether (DOL / DME, volume ratio of 1:1) containing 1mol / L lithium di(trifluoromethylsulfonyl)imide and 0.2mol / L lithium nitrate.
[0053] 2. The rate performance and cycle stability of the lithium-sulfur battery samples prepared as described above were tested by constant current charge and discharge tests.
[0054] (1) Rate performance test:
[0055] The lithium-sulfur battery sample was charged and discharged for 5 cycles at 1C in the voltage range of 1.7-2.7V. The charge specific capacity of the corresponding charge and discharge cycle was recorded, and the average charge specific capacity of the 5 cycles was calculated:
[0056] The average charge capacity of 5 cycles at 1C = the sum of the charge capacity from the 1st cycle to the 5th cycle / 5;
[0057] Similarly, the charge-discharge cycle was repeated for 5 cycles at 2C and 3C, respectively, and the average charge specific capacity of 5 cycles at 2C and 3C was measured.
[0058] (2) Cyclic stability test:
[0059] The lithium-sulfur battery sample was charged and discharged for 2 cycles at 0.1C and 0.2C in the voltage range of 1.7-2.7V (activation). Then the lithium-sulfur battery sample was cycled for 150 cycles at 0.5C, and the capacity retention rate after the first 150 cycles at 0.5C was recorded to characterize the cycle stability.
[0060] Capacity retention rate = (charge specific capacity at the 150th cycle / charge specific capacity at the 1st cycle) × 100%.
[0061] 3. In the present invention, the UV-visible spectroscopy diffuse reflectance test instrument is a UV-visible near-infrared spectrometer purchased from Agilent, instrument model: Cary 5000, wavelength test range: 200-800nm.
[0062] (Example 1)
[0063] Preparation of Fe-doped lithium-containing MFI molecular sieve:
[0064] 5g of H-type MFI molecular sieve with a silicon-aluminum atomic ratio of 10 was mixed with 100mL of 2.0mol / L oxalic acid solution, reacted at 60°C for 2h, and then centrifuged, washed, and dried to obtain precursor I. Precursor I was then mixed with 0.30g of ferrocene powder and calcined at 500°C for 6h to obtain Fe-doped MFI molecular sieve. Subsequently, the Fe-doped MFI molecular sieve was lithium-ion exchanged with 0.5mol / L LiCl solution (liquid-to-solid weight ratio of 20) at 80°C for 2h, then centrifuged and washed, and the sample obtained after repeated lithium ion exchange twice was dried at 100°C for 24 hours to obtain Fe-doped lithium-containing MFI molecular sieve.
[0065] Preparation of molecular sieve modified membrane:
[0066] (1) grinding and mixing 0.35 g of Fe-doped lithium-containing MFI molecular sieve and 0.1 g of graphene in a mortar to obtain 0.45 g of a mixture;
[0067] (2) dispersing the above mixture and 0.05 g of polyvinylidene fluoride in N-methylpyrrolidone, stirring and mixing evenly to obtain a coating slurry;
[0068] (3) The coating slurry is uniformly coated on one side of the polyethylene / polypropylene substrate film by a doctor blade method, and then dried to remove the solvent to obtain a molecular sieve modified diaphragm, wherein the thickness of the Fe-doped lithium-containing MFI molecular sieve / graphene composite layer is 10 μm.
[0069] The Fe content in the molecular sieve obtained in Example 1 is 1.8%, and the Li content is 1.0%.
[0070] The UV-visible diffuse reflectance spectrum of the molecular sieve obtained in Example 1 is shown in Figure 1 .
[0071] Performance test of molecular sieve modified membrane:
[0072] As described above, the prepared molecular sieve modified separator was used to assemble a lithium-sulfur battery sample and its rate performance and cycle stability were tested. The specific test results are shown in Table 1.
[0073] [Example 2]
[0074] Compared with Example 1, the only difference is that the ferrocene powder is replaced by an equal amount of dimethyltin dichloride to obtain a Sn-doped lithium-containing MFI molecular sieve, and the corresponding molecular sieve modified diaphragm is prepared.
[0075] The Sn content in the molecular sieve obtained in Example 2 is 3.2%, and the Li content is 1.0%.
[0076] The UV-visible diffuse reflectance spectrum of the molecular sieve obtained in Example 2 is shown in Figure 2 .
[0077] Performance test of molecular sieve modified membrane:
[0078] As described above, the prepared molecular sieve modified separator was used to assemble a lithium-sulfur battery sample and its rate performance and cycle stability were tested. The specific test results are shown in Table 1.
[0079] [Example 3]
[0080] Compared with Example 1, the only difference is:
[0081] In the preparation of heteroatom-doped molecular sieves, the H-type MFI molecular sieve with a silicon-aluminum atomic ratio of 10 is replaced by the H-type MWW molecular sieve with a silicon-aluminum atomic ratio of 35;
[0082] In the preparation of the molecular sieve modified membrane, the amount of molecular sieve in step (1) is adjusted to 0.42 g, and the amount of graphene is adjusted to 0.03 g; the thickness of the composite layer obtained in step (3) is 25 μm.
[0083] The Fe content in the molecular sieve obtained in Example 3 is 1.8%, and the Li content is 0.3%.
[0084] The UV-visible diffuse reflectance spectrum of the molecular sieve obtained in Example 3 is similar to Figure 1 .
[0085] Performance test of molecular sieve modified membrane:
[0086] As described above, the prepared molecular sieve modified separator was used to assemble a lithium-sulfur battery sample and its rate performance and cycle stability were tested. The specific test results are shown in Table 1.
[0087] [Example 4]
[0088] Compared with Example 1, the only difference is:
[0089] In the preparation of heteroatom-doped molecular sieves, the H-type MFI molecular sieve with a silicon-aluminum atomic ratio of 10 is replaced by the H-type FAU molecular sieve with a silicon-aluminum atomic ratio of 25;
[0090] In the preparation of the molecular sieve modified membrane, the amount of molecular sieve in step (1) is adjusted to 0.40 g, and the amount of graphene is adjusted to 0.05 g; the thickness of the composite layer in step (3) is 15 μm.
[0091] The Fe content in the molecular sieve obtained in Example 4 is 1.8%, and the Li content is 0.4%.
[0092] The UV-visible diffuse reflectance spectrum of the molecular sieve obtained in Example 4 is similar to Figure 1 .
[0093] Performance test of molecular sieve modified membrane:
[0094] As described above, the prepared molecular sieve modified separator was used to assemble a lithium-sulfur battery sample and its rate performance and cycle stability were tested. The specific test results are shown in Table 1.
[0095] [Example 5]
[0096] Compared with Example 1, the only difference is:
[0097] In the preparation of heteroatom-doped molecular sieves, the H-type MFI molecular sieve with a silicon-aluminum atomic ratio of 10 is replaced by the H-type MOR molecular sieve with a silicon-aluminum atomic ratio of 15;
[0098] In the preparation of the molecular sieve modified membrane, the amount of molecular sieve in step (1) is adjusted to 0.30 g, and the amount of graphene is adjusted to 0.15 g; the thickness of the composite layer in step (3) is 5 μm.
[0099] The Fe content in the molecular sieve obtained in Example 5 is 1.8%, and the Li content is 0.7%.
[0100] The UV-visible diffuse reflectance spectrum of the molecular sieve obtained in Example 5 is similar to Figure 1 .
[0101] Performance test of molecular sieve modified membrane:
[0102] As described above, the prepared molecular sieve modified separator was used to assemble a lithium-sulfur battery sample and its rate performance and cycle stability were tested. The specific test results are shown in Table 1.
[0103] [Example 6]
[0104] Compared with Example 1, the only difference is that the heteroatom molecular sieve is not subjected to lithium ion exchange, and the obtained Fe-doped MFI molecular sieve is directly used to prepare the corresponding molecular sieve modified diaphragm.
[0105] Performance test of molecular sieve modified membrane:
[0106] As described above, the prepared molecular sieve modified separator was used to assemble a lithium-sulfur battery sample and its rate performance and cycle stability were tested. The specific test results are shown in Table 1.
[0107] [Example 7]
[0108] Compared with Example 1, the only difference is that the preparation process of Fe-doped lithium-containing MFI molecular sieve is as follows:
[0109] 5g of H-type MFI molecular sieve with a silicon-aluminum atomic ratio of 10 was mixed with 100mL of 1.0mol / L oxalic acid solution, reacted at 60°C for 2h, and then centrifuged, washed, and dried to obtain precursor I. Precursor I was then mixed with 0.15g of ferrocene powder and calcined at 500°C for 6h to obtain Fe-doped MFI molecular sieve. Subsequently, the Fe-doped MFI molecular sieve was lithium-ion exchanged with 0.1mol / L LiCl solution (liquid-to-solid weight ratio of 10) at 80°C for 2h, then centrifuged and washed, and the sample obtained after repeated lithium ion exchange twice was dried at 100°C for 24 hours to obtain Fe-doped lithium-containing MFI molecular sieve.
[0110] The preparation process of the molecular sieve modified membrane is the same as that in the embodiment.
[0111] The Fe content in the molecular sieve obtained in Example 7 is 0.9%, and the Li content is 0.1%.
[0112] Performance test of molecular sieve modified membrane
[0113] As described above, the prepared molecular sieve modified separator was used to assemble a lithium-sulfur battery sample and its rate performance and cycle stability were tested. The specific test results are shown in Table 1.
[0114] [Example 8]
[0115] Compared with Example 1, the only difference is that the preparation process of Fe-doped lithium-containing MFI molecular sieve is as follows:
[0116] 5g of H-type MFI molecular sieve with a silicon-aluminum atomic ratio of 5 was mixed with 200mL of 4.0mol / L oxalic acid solution, reacted at 60°C for 2h, and then centrifuged, washed, and dried to obtain precursor I. Precursor I was then mixed with 1.2g of ferrocene powder and calcined at 500°C for 6h to obtain Fe-doped MFI molecular sieve. Subsequently, the Fe-doped MFI molecular sieve was lithium-ion exchanged with 1.0mol / L LiCl solution (liquid-to-solid weight ratio of 20) at 80°C for 2h, then centrifuged and washed, and the sample obtained after repeated lithium ion exchange twice was dried at 100°C overnight to obtain Fe-doped lithium-containing MFI molecular sieve.
[0117] The preparation process of the molecular sieve modified membrane is the same as that in Example 1.
[0118] The Fe content in the molecular sieve obtained in Example 8 is 7.2%, and the Li content is 1.9%.
[0119] Performance test of molecular sieve modified membrane
[0120] As described above, the prepared molecular sieve modified separator was used to assemble a lithium-sulfur battery sample and its rate performance and cycle stability were tested. The specific test results are shown in Table 1.
[0121] [Comparative Example 1]
[0122] Compared with Example 1, the only difference is that: there is no need to prepare a molecular sieve modified diaphragm, but the molecular sieve modified diaphragm is directly replaced by a polyethylene / polypropylene matrix membrane to assemble a lithium-sulfur battery sample and perform a performance test. The test results are shown in Table 1.
[0123] [Comparative Example 2]
[0124] Compared with Example 1, the only difference is that the prepared molecular sieve is different, 5g of Na-type MFI molecular sieve with a silicon-aluminum atomic ratio of 10 is immersed in 16mL of 0.1mol / L ferric chloride solution, dried under 80°C air condition, and then further treated at 700°C air condition for 2h to obtain an MFI molecular sieve loaded with iron oxide. The Fe content in the obtained molecular sieve is the same as that in Example 1.
[0125] The UV-visible diffuse reflectance spectrum of the molecular sieve obtained in Comparative Example 2 is shown in Figure 3 .
[0126] Performance test of molecular sieve modified membrane:
[0127] As described above, the prepared molecular sieve modified separator was used to assemble a lithium-sulfur battery sample and its rate performance and cycle stability were tested. The specific test results are shown in Table 1.
[0128] [Comparative Example 3]
[0129] Compared with Example 1, the only difference is that: the preparation of Fe-doped lithium-containing MFI molecular sieve is specifically as follows: 5g of H-type MFI molecular sieve with a silicon-aluminum atomic ratio of 10 is mixed with 100mL of concentrated nitric acid (65%), reacted at 100°C for 24h, centrifuged, washed and dried to obtain precursor I. Subsequently, precursor I is mixed with 0.30g of ferrocene powder and calcined at 200°C for 6h to obtain precursor II. Subsequently, precursor II is subjected to lithium ion exchange with 0.5mol / L LiCl solution (liquid-to-solid volume ratio of 20) at 80°C for 2h, then centrifuged and washed, and the sample obtained after repeated lithium ion exchange twice is dried at 100°C overnight to obtain Fe-doped lithium-containing MFI molecular sieve.
[0130] The Fe content in the molecular sieve obtained in Comparative Example 3 is 2.0%, and the Li content is 1.5%.
[0131] The ultraviolet-visible (UV-vis) diffuse reflectance spectrum of the molecular sieve obtained in Comparative Example 3 shows an Fe absorption peak at 260±5nm.
[0132] Performance test of molecular sieve modified membrane:
[0133] As described above, the prepared molecular sieve modified separator was used to assemble a lithium-sulfur battery sample and its rate performance and cycle stability were tested. The specific test results are shown in Table 1.
[0134] [Comparative Example 4]
[0135] Compared with Example 1, the only difference is that: the H-type MFI molecular sieve with a silicon-aluminum atomic ratio of 10 is directly subjected to lithium ion exchange with 0.5 mol / L LiCl solution (liquid-to-solid weight ratio of 20) at 80°C for 2 hours, and then centrifuged and washed. The sample obtained after repeating the lithium ion exchange twice is dried at 100°C overnight to obtain a lithium-containing MFI molecular sieve.
[0136] The content of Li in the molecular sieve obtained in Comparative Example 4 is 1.0%.
[0137] Performance test of molecular sieve modified membrane:
[0138] As described above, the prepared molecular sieve modified separator was used to assemble a lithium-sulfur battery sample and its rate performance and cycle stability were tested. The specific test results are shown in Table 1.
[0139] Table 1 Electrochemical performance test results of lithium-sulfur batteries obtained in each example
[0140]
[0141] The above describes the specific implementation of the present invention in detail, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the various technical features being combined in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A battery separator, comprising a polymer matrix film and a composite layer distributed on one side surface of the polymer matrix film, wherein the composite layer comprises a heteroatom-doped molecular sieve and a conductive carbon material, wherein the heteroatom is located in the crystal framework of the molecular sieve.
2. The battery separator according to claim 1, characterized in that In the heteroatom-doped molecular sieve, the heteroatom is at least one of Fe and Sn heteroatoms, preferably Fe or Sn; the topological structure of the molecular sieve is selected from at least one of MFI, MWW, FAU and MOR, preferably MFI.
3. The battery separator according to claim 1, characterized in that The characteristic absorption peaks of Fe appear at 247±5nm, 278±5nm and 621±5nm in the ultraviolet-visible diffuse reflectance spectrum of the heteroatom-doped molecular sieve; the characteristic absorption peak of Sn appears at 206±2nm in the ultraviolet-visible diffuse reflectance spectrum of the heteroatom-doped molecular sieve.
4. The battery separator according to claim 1, characterized in that The thickness of the composite layer is 1-40 μm, preferably 3-20 μm.
5. The battery separator according to claim 1, characterized in that: In the composite layer, the mass ratio of the conductive carbon material to the heteroatom-doped molecular sieve is 1:(1-20), preferably 1:(3-9).
6. The battery separator according to claim 1, characterized in that: In the heteroatom-doped molecular sieve, the content of heteroatoms is 0.5%-10.0%, preferably 1.0%-7.0%, based on the weight of the heteroatom-doped molecular sieve; And / or, the heteroatom-doped molecular sieve contains lithium, and the content of lithium as an element is 0.1%-5.0%, preferably 0.2%-1.8%, based on the weight of the heteroatom-doped molecular sieve.
7. The battery separator according to claim 1, characterized in that: The material of the polymer matrix film is at least one of polyethylene, polypropylene, polyimide, polyacrylonitrile, polyethylene terephthalate, polytetrafluoroethylene, and polyvinylidene fluoride, preferably polyethylene, polypropylene, or a polyethylene / polypropylene composite material; And / or, the conductive carbon material is at least one of graphene, carbon nanotubes, carbon nanofibers, acetylene black, Super P, and Ketjen black, preferably graphene.
8. The method for preparing the battery separator according to any one of claims 1 to 7, comprising: (1) mixing a heteroatom-doped molecular sieve with a conductive carbon material to obtain a mixture; (2) dispersing the mixture and the binder in a solvent to obtain a coating slurry; (3) coating the coating slurry on one surface of the polymer substrate film and drying it to obtain the battery separator.
9. The preparation method according to claim 8, characterized in that: The solvent in step (2) is at least one of deionized water, anhydrous ethanol, N,N-dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide, and N-methylpyrrolidone, preferably N-methylpyrrolidone; And / or, the binder in step (2) is at least one of polyvinyl alcohol, carboxymethyl cellulose, polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl pyrrolidone, styrene-butadiene rubber and polyacrylate, preferably polyvinylidene fluoride; And / or, the coating in step (3) is at least one of a casting method, a blade coating method, a spray coating method, and a spin coating method, preferably a blade coating method.
10. The preparation method according to claim 8, characterized in that: The preparation method of heteroatom-doped molecular sieve comprises: (S1) H-type molecular sieve reacts with an acid solution to obtain precursor I; (S2) The obtained precursor I is mixed with a heteroatom salt and calcined to obtain a heteroatom-doped molecular sieve.
11. A lithium-sulfur battery, characterized in that: The invention comprises a positive electrode, a negative electrode and a battery separator according to any one of claims 1 to 7 located between the positive electrode and the negative electrode.
Citation Information
Patent Citations
Membrane for lithium-sulfur battery and preparation method of membrane
CN103490027A
An application of a molecular sieve composite porous membrane in a lithium-sulfur battery
CN107546356A
Metal element modified ZSM-5 molecular sieve composite membrane as well as preparation method and application thereof
CN102350229A
Lithium ion battery and anode thereof
CN102709521A
Metal-doped silicon oxide molecular sieve / sulfur carbon compound and preparation method and application thereof
CN107579233A